Communication barriers experienced by paediatric palliative care staff when interacting with children, young people and families: a literature review. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Patel, Reena; Coad, Jane; Murray, Sarah
Abstract : Background: A recent Department of Health funded evaluation of West Midlands Children and Young People's Palliative Care services disclosed that staff reported concerns about their ability to effectively communicate with children and families. Few studies have fully explored the problem of communication barriers in paediatric palliative care, particularly the detrimental effects of poor interaction between staff and families on children's health and well-being. A literature review was undertaken to expand the current body of knowledge about staff to patient communications in paediatric palliative care. Aim: First, to explore the literature surrounding communication barriers experienced by palliative care staff, children and families and second, to identify directions for future research. Methods: Combinations of selected key words were systematically applied to identify research on communication barriers experienced by paediatric palliative care staff and families. Articles meeting the inclusion criteria were read and descriptively summarised using a data extraction sheet. A narrative synthesis was conducted by examining commonly reported communication issues which were then condensed into five overarching themes. Results: Limited research is available that explores the perspectives of staff, children and their families about perceived communication barriers in paediatric palliative care services. However, the primary issues to emerge from available literature included perceived lack of staff knowledge about emotional support, style in which staff conveyed diagnostic information, the constant change of professionals interacting with families and the lack of formal training and guidelines for staff to meet the needs of children and families with additional complex care needs. Conclusion: There is an under-representation of research in communicating with children, young people and families in palliative care. Improvements in staff education regarding communication skills and individualised palliative care plans for children and families may help to overcome some of the exacerbating communication barriers currently obstructing the attainment of high quality paediatric palliative care.